Vaccine Diplomacy as New Soft Power Effort of US in Dealing with China in Southeast Asia - Cahayani, Ica (Parahyangan Center for International Studies, 2024)
The COVID-19 pandemic and developed countries' response to the crisis reveal that the landscape of global health governance is changing into a political realm. As countries around the world struggle to secure vaccines to break the COVID-19 chain, superpowers are actively distributing vaccines internationally in an act known as